Paleoceanographic changes across OAE 2 inferred from resilient foraminifera and XRF data at southern high latitudes (IODP Sites U1513 and U1516, Mentelle Basin, SW Australia) - Giulia Amaglio; Maria Rose Petrizzo; Erik Wolfgring; Ann Holbourn; Wolfgang Kuhnt (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)
The Oceanic Anoxic Event 2 (OAE 2), across the Cenomanian-Turonian boundary interval, was characterized by global environmental perturbations in the carbon cycle that affected the abundance and biodiversity of marine biota and their paleoecological preferences. International Ocean Discovery Program (IODP) Sites U1513 and U1516 in the Mentelle Basin (offshore SW Australia) reveal a continuous foraminiferal record that document the adaptative response of biota, suitable to reconstruct paleoenvironmental conditions in the water column and at the seafloor. Below and during the initial part of the OAE 2, we do not observe changes in the benthic foraminiferal assemblages dominated by Gavelinella, Gyroidinoides and Stensioeina. Agglutinated foraminifera are rare, whereas Microhedbergella and Muricohedbergella dominate the planktonic foraminiferal assemblage, indicating possible eutrophication episodes below and during the OAE 2 associated to an increase in terrigenous sediments. However, a positive peak in Zr/Rb ratios, the unique occurrence of Stensioeina truncata, and the increase in epifaunal- infaunal ratio, particularly at Site U1516, indicate a greater eolian transportation of sediments and an enhanced oxygenation at the seafloor, which might be related to the identification of the Plenus Cold Event (PCE) at high latitudes. An interval of low CaCO3 content within the peak of OAE 2 is characterized by the absence of foraminifera and dominance of siliceous organisms. It is also marked by a sudden enhancement of the hydrological cycle, probably causing a shoaling of the Calcite Compensation Depth (CCD). However, Site U1516 shows few samples with a change in the planktonic and benthic foraminiferal assemblage. Above this interval, both sites are characterized by a different benthic foraminiferal assemblage with the occurrence of Conorboides claytonensis in the uppermost part of OAE 2. At Site U1513, epi-infaunal ratio increase, planktonic foraminifera show the highest diversification, rainfall decreases, indicating a ...